Heretic : why Islam needs a reformation now - Hirsi Ali, Ayaan
Today, Hirsi Ali argues, the world's 1.6 billion Muslims can be divided into a minority of extremists, a majority of observant but peaceable Muslims, and a few dissidents who risk their lives by questioning their own religion. But there is only one Islam, and as Hirsi Ali shows, there is no denying that some of its key teachings -- not least the duty to wage holy war -- inspire violence not just in the Muslim world but in the West as well. For centuries it has seemed that Islam is immune to historical change. But Hirsi Ali is surprisingly optimistic. She has come to believe that a Muslim "Reformation" -- a revision of Islamic doctrine aimed at reconciling the religion with modernity -- is at hand, and may even already have begun. Partly in response to the barbaric atrocities of Islamic State and Boko Haram, Muslims around the world have at last begun to speak out for religious reform. Meanwhile, events in the West, such as the shocking Charlie Hebdo massacre, have forced Western liberals to recognize that political Islam poses a mortal threat to free speech. Yet neither Muslim reformers nor Western liberals have so far been able to articulate a coherent program for a Muslim Reformation. This is where Heretic comes in. Boldly challenging centuries of theological orthodoxy, Ayaan Hirsi Ali proposes five key amendments to Islamic doctrine that Muslims must make if they are to bring their religion out of the seventh century and into the twenty-first. She also calls upon the Western world to end its appeasement of radical Islamists -- and to drop the bogus argument that those who stand up to them are guilty of "Islamophobia." It is the Muslim reformers who need our backing, she argues, not the opponents of free speech. Interweaving her own experiences, historical analogies, and powerful examples from contemporary Muslim societies and cultures, Heretic is not so much a call to arms as a passionate plea for peaceful change and a new era of global tolerance.